173k views
1 vote
Helppp plsssss!!show your work.
Thanks

Helppp plsssss!!show your work. Thanks-example-1
User BabakHSL
by
4.7k points

2 Answers

3 votes

The expression for
(f+g)(x) is simply the sum of the expressions of
f(x) and
g(x).

So, you have


(f+g)(x) = f(x) + g(x) = (3x^2-2x+4)+(5x^2+6x-8) = 8x^2+4x-4

User Steven Jiang
by
5.2k points
2 votes

You are basically just adding, so combine like terms.

3x^2 + 5x^2 = 8x^2

6x - 2x = 4x

4 - 8 = -4

So the answer is D.

User Nathan Howell
by
5.3k points